Religion, Politics, and Society: The Role of Political Islam in the Sudanese Revolution of December 2018 and Its Aftermath - Bakheit Mohammed Nur (Modern Africa, 2023)
December 2018 marked a new direction in Sudan’s political landscape as thousands of people revolted against President Omar al-Bashir and the Islamist regime that had ruled the country since 1989. Under authoritarian rule, Sudan suffered from genocide, war crimes, human rights violations and economic stagnation. As a result, Sudanese opposition groups organised demonstrations in 2018 to protest repression and demand change. This revolution galvanised unprecedented support from a wide variety of socio-cultural groups across the country. Protestors together with the army succeeded in ousting President al-Bashir from power in April 2019, setting in motion a process for political change in Sudan. This article analyses the practices performed by protestors in 2018 and 2019 and examines the social-cultural, political and religious dimensions of the Sudanese revolution. It also explores how the revolution’s protagonists contested the role of political Islam and how its antagonists reaffirmed their Islamo-political ideology in counter-revolutionary activities. The discussion also includes a violent atmosphere of the current war, which erupted in April 2023.